The Role of Government and Society in Countermeasures and Prevention of Criminal Acts of Terrorism According to Law Number 5 of 2018 - SETIYONO, Joko; NABELA, Nadia (Indonesia Strategic Sustainability, 2023)
The criminal act of terrorism is a serious crime and an extraordinary crime which has an adverse impact on the sovereignty of the state and the security of the citizens' livelihood. The responsibility of the state in protecting all citizens is an obligation mandated in the constitution (1945 Constitution). Law Number 5 of 2018 is a legal umbrella in carrying out law enforcement efforts, countermeasures and measures to prevent criminal acts of terrorism. The government plays an active role in taking strategic steps to tackle and prevent criminal acts of terrorism by revising Law no. 15 of 2003 became Law Number 5 of 2018, forming the Special Anti-Terror Special Detachment 88 Task Force, as well as the National Counterterrorism Agency (BNPT). The community also plays an active role in efforts to prevent criminal acts of terrorism by having high awareness of the law, increasing knowledge and awareness of the dangers of terrorism, so that they can carry out early detection of potential terrorism and report things that are considered suspicious in the surrounding environment to the authorities.